2011
DOI: 10.1002/app.33734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrophilic chain length on the aqueous solution behavior of block amphiphilic copolymers PMMA‐b‐PDMAEMA

Abstract: A series of amphiphilic block copolymers, polymethyl methacrylate (PMMA)-b-poly [2-(dimethylamino)ethyl methacrylate] (PDMAEMA), were synthesized by atom transfer radical polymerization (ATRP) method. Surface tension, dynamic light scattering (DLS), transmission electron microscope (TEM), and atomic force microscopy (AFM) studies were performed to investigate the aqueous micellar behavior of these block amphiphiles. At a fixed degree of polymerization (DP) of PMMA block (DP ¼ 55), the PDMAEMA block length was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
(26 reference statements)
5
15
0
1
Order By: Relevance
“…Moreover, they first reported the critical micelle concentration (cmc) dependence on the chemical structure of PMMA‐ b ‐PDMAEMA with non‐protein nitrogen (NPN) fluorescence . Zhang et al . found that the average sizes and micromorphology of PMMA‐ b ‐PDMAEMA aggregates at different pH depended strongly on the solvent nature and the PDMAEMA chain length.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they first reported the critical micelle concentration (cmc) dependence on the chemical structure of PMMA‐ b ‐PDMAEMA with non‐protein nitrogen (NPN) fluorescence . Zhang et al . found that the average sizes and micromorphology of PMMA‐ b ‐PDMAEMA aggregates at different pH depended strongly on the solvent nature and the PDMAEMA chain length.…”
Section: Introductionmentioning
confidence: 99%
“…This can be justified by the packing parameter theory . Xiao et al . have observed a similar behavior for the micellization of a series of poly(methyl methacrylate)‐ b ‐poly[2‐(dimethylamino)ethyl methacrylate] diblock copolymers with fixed hydrophobic chain length and varying the hydrophilic segment length in aqueous solution, where the micelle size was observed to decrease with increasing the hydrophilic chain length.…”
Section: Resultsmentioning
confidence: 70%
“…Of these living polymerization techniques, atom transfer radical polymerization (ATRP) 7 and RAFT 8 are generally considered to be the best strategies to obtain functional polymeric systems for defined applications. Amphiphilic copolymers based on PDMAEMA, such as PMMA-b-DMAEMA 3,9 , PDMAEMA-b-PCL-b-PDMAEMA 10 , PTFEco-PDMAEMA 11 , and PS-b-PDMAEMA 12 , have been described, with the aim of studying self-assembly behavior at different solution pH values. The LCST of PMMA-b-PDMAEMA copolymers synthesized by RAFT was found to be affected by ionic strength, pH and the nature of the ion 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al 12 showed that on adjusting certain parameters, such as the solvent, charge density and pH, specific changes in the structure of the aggregations can be obtained for PS-b-PDMAEMA copolymers obtained by ATRP. Xiao and others synthesized PMMA-b-PDMAEMA by ATRP and investigated the effects of PMMA or PDMAEMA block length on the aggregate formation 9 . However, studies related to new mechanisms of controlled polymerization of VCL are still scarce, due to several factors including the fact that VCL is an unconjugated monomer and its propagating radical is poorly stabilized and, as a consequence, very reactive.…”
Section: Introductionmentioning
confidence: 99%